Peran Teknologi Kultur Daging dalam Percepatan Ketahanan Pangan Global - Puput Fuji Aslamiah; Raden Elfa Shafira Maulina; Yasmin Pajrin Maulani; Tri Cahyanto (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2025)
Rapid global population growth has led to climate change and agricultural land degradation, posing significant challenges to the stability of global food security. The traditional livestock sector is known to absorb high levels of greenhouse gas emissions that can accelerate natural resource degradation and require innovative and sustainable approaches to meet the demand for animal protein. This study aims to analyze the contribution of cultured meat technology as an ethical and environmentally friendly alternative to improving global food security. This study uses a desk study method that addresses the technical, social, economic, and ethical aspects of cultured meat production. The analysis results indicate that the application of this technology has the potential to reduce land use and carbon emissions by up to 70% compared to conventional livestock systems, in addition to reducing animal suffering and the risk of zoonotic disease transmission. However, its application still faces several obstacles, such as high production costs, dependence on whey-based culture media, and difficulties in halal certification and public acceptance. These findings underscore the importance of synergy between scientists, governments, and religious authorities to ensure the safety, effectiveness, and equivalence of technology with ethical principles and socio-cultural values. With strong regulatory support and ongoing research, cultured meat technology has the potential to be a strategic solution for building a resilient, equitable, and environmentally responsible global food system.